THE EFFECTIVENESS OF THE STORYTELLING METHOD USING FOLKTALES ON EARLY CHILDHOOD EMPATHY BEHAVIOR AT VILLA BETA KINDERGARTEN PADANG CITY - Muty risky fitriani; Maisoni, M Farhan Putra; Bakri, Akmal; Prima Aulia (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Storytelling provides opportunities for children to develop empathy for the world around them. This study was conducted with the aim of seeing the effectiveness of the storytelling approach on early childhood empathy behavior at Villa Beta Kindergarten, Padang City. Respondents in this study were 7 students of Villa Beta Kindergarten with 5 female respondents and 2 male respondents. The research design used in this study is an experimental design of the One-Group Pretest-Posttest Design type. Data collection was carried out using an empathy scale modified from Davis (1980), the empathy scale consists of four main aspects, namely perspective taking, fantasy, empathic concern, and personal distress. The resulting significance is p = 0.028 <0.05 so that the results obtained from this study are that there are significant differences in children's empathy behavior after treatment in the form of storytelling methods.